Risk-free rates and convenience yields around the world - William Diamond; Peter Van Tassel (Federal Reserve Bank of New York, 2022)
This paper constructs risk-free interest rates implicit in index option prices for ten of the major G11 currencies. We compare these rates to the yields of government bonds to provide international estimates of the convenience yield earned by safe assets. Average convenience yields across countries are highly correlated with the average interest rate in each country, ranging from 2 basis points in low-rate Switzerland to 61 basis points in high-rate Australia, with the moderate-rate United States providing a middling 34 basis points. For each country, a covered interest parity (CIP) deviation constructed from its option-implied rates and those of the United States is negative, with these negative CIP deviations growing sharply in periods of financial distress, including the 2020 COVID crisis when convenience yields themselves remained moderate. We conclude that risk-free discount rates in the United States are especially low due to its central position in the global financial system, particularly during financial crises, but that U.S. safe assets do not earn an unusually large convenience yield in addition.
Keywords: G12; G15; C58; 330; risk-free rates; convenience yields; covered interest rate parity; options